Comparison of the 24-Style Tai Chi intervention based on various promotion approaches on college students’ mental health: A randomized controlled trial - Kai Xu; Zetong Sun; Defeng Dong; Zhiyuan Tan; Jundi Chen; Carlo Castagna; Peter Krustrup; Jun Xu; Shuang Wei (PLoS ONE, 2026)
Background The escalating pace of academic pressures and social life have intensified mental health challenges among college students, including widespread anxiety and depression. Non-pharmacological interventions, such as exercise therapy, have gained prominence, with 24-Style Tai Chi emerging as a promising mind-body exercise due to its simplicity and potential mental health benefits. However, its effectiveness across various promotion approaches in higher education settings remains underexplored. Objective This study aimed to evaluate the impact of different 24-Style Tai Chi promotion methods (on-site, online, mixed, and independent practice) on college students’ mental health, assess intervention efficacy, and identify an optimal promotion strategy. Methods A randomized controlled trial (RCT) involving 250 college students from Shandong Sport University was conducted over 8 weeks. Participants were allocated to On-Site Promotion Group (Offline-PG), Online Promotion Group (Offline-PG), Mixed Promotion Group (MPG), Independent Practice Group (IPG), or Control Group (CG). Mental health was assessed using the Self-Rating Anxiety Scale (SAS), Self-Rating Depression Scale (SDS), and General Self-Efficacy Scale (GSES) at baseline, 4 and 8 weeks, and follow-up. Data were analyzed using one-way ANOVA, repeated measures ANOVA (RM-ANOVA), and regression analysis to evaluate intervention effects and participation impacts. Results Offline-PG (90% attendance) and MPG (84% attendance) showed significant reductions in anxiety (SAS: Offline-PG 34.8 ± 6.3, MPG 36.2 ± 7.0, P < 0.01) and depression (SDS: Offline-PG 33.7 ± 6.9, MPG 34.9 ± 7.2, P < 0.05) by week 8. Online-PG (72% attendance) and MPG demonstrated significant self-efficacy improvements (GSES: Online-PG 36.1 ± 5.2, MPG 35.5 ± 5.6, P < 0.01). IPG (60% attendance) showed no significant changes. ANOVA revealed inter-group differences (SAS F = 6.45, P = 0.004; SDS F = 5.32, P = 0.009; GSES F = 6.74, P = 0.003), with RM-ANOVA confirming time effects. Regression analysis indicated participation strongly correlated with anxiety and depression reductions in Offline-PG (R = 0.62, P = 0.003) and MPG (R = 0.58, P = 0.004) and self-efficacy gains in Online-PG and MPG (R = 0.67, P = 0.002). Conclusion 24-Style Tai Chi effectively improves college students’ mental health, with on-site and mixed approaches excelling in reducing anxiety and depression, and online and mixed approaches enhancing self-efficacy. A hybrid promotion strategy is recommended to optimize participation and outcomes. Registration number: TCTR20250306005; https://thaiclinicaltrials.org/ .